A Mycobacterium avium subsp. paratuberculosis Predicted Serine Protease Is Associated with Acid Stress and Intraphagosomal Survival - Kugadas, Abirami; Lamont, Elise A.; Bannantine, John P.; Shoyama, Fernanda M.; Brenner, Evan; Janagama, Harish K.; Sreevatsan, Srinand (Frontiers in Cellular and Infection Microbiology, 2016)
Abstract The ability to maintain intra-cellular pH is crucial for bacteria and other microbes to survive in diverse environments, particularly those that undergo fluctuations in pH. Mechanisms of acid resistance remain poorly understood in mycobacteria. Although studies investigating acid stress in M. tuberculosis are gaining traction, few center on Mycobacterium avium subsp. paratuberculosis (MAP), the etiological agent of chronic enteritis in ruminants. We identified a MAP acid stress response network involved in macrophage infection. The central node of this network was MAP0403, a predicted serine protease that shared an 86% amino acid identity with MarP in M. tuberculosis. Previous studies confirmed MarP as a serine protease integral to maintaining intra-bacterial pH and survival in acid in vitro and in vivo. We show that MAP0403 is upregulated in infected macrophage and MAC-T cells and coincided with phagosome acidification. Treatment of mammalian cells with bafilomcyin A1, a potent inhibitor of phagosomal vATPases, diminished MAP0403 transcription. MAP0403 expression was also noted in acidic medium. A surrogate host, M. smegmatis mc2 155, was designed to express MAP0403 and when exposed to either macrophages or in vitro acid stress had increase bacterial cell viability, which corresponds to maintenance of intra-bacterial pH in acidic (pH = 5) conditions. These data suggest that MAP0403 may be the equivalent of MarP in MAP. Future studies confirming MAP0403 as a serine protease and exploring its structure and possible substrates are warranted.